AVALIAÇÃO QUÍMICA DO ÓLEO ESSENCIAL DAS FOLHAS E CAULES DA GUABIROBA- CAPOTEIRA - SCHOTT, Joice de Oliveira; ADÃO, Cintia Cristina Domiciano; MACIEL, Luênery Henrique de Oliveira; SILVA, Rogério Cesar de Lara da Silva (ANAIS DO ENIC, 2022)
-